2000
DOI: 10.1093/gerona/55.3.b135
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Increase in Infarct Volume Following Photochemically Induced Cerebral Infarction: Putative Role of Astroglia

Abstract: This study demonstrates that the photochemically induced model of stroke is an extremely viable method of inducing cerebral infarction in old animals. The lesions are reproducible both in terms of location and size and compatible with long-term survival of the animal. With this model we demonstrated, one week following surgery, a significantly larger infarct in rats 20 and 24 months of age compared to 4-month-old rats. The older rats also sustained greater neurologic deficits as assessed on a rotarod task. Old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 38 publications
6
27
1
1
Order By: Relevance
“…The behavioral outcome in aged animals has been reported to be impaired compared with young animals (Zhang et al, 2005;Popa-Wagner et al, 2007;Petcu et al, 2008). The effect of age on the infarct size in preclinical studies has resulted in somewhat contradictory findings depending on the ischemia model used (Davis et al, 1995;Kharlamov et al, 2000;Shapira et al, 2002;Rosen et al, 2005). In this current study, the infarct size in aged mice was similar compared with young mice, a finding that is in agreement with a previously published study using a photothrombotic model of brain ischemia (Zhao et al, 2005).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The behavioral outcome in aged animals has been reported to be impaired compared with young animals (Zhang et al, 2005;Popa-Wagner et al, 2007;Petcu et al, 2008). The effect of age on the infarct size in preclinical studies has resulted in somewhat contradictory findings depending on the ischemia model used (Davis et al, 1995;Kharlamov et al, 2000;Shapira et al, 2002;Rosen et al, 2005). In this current study, the infarct size in aged mice was similar compared with young mice, a finding that is in agreement with a previously published study using a photothrombotic model of brain ischemia (Zhao et al, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…It is thus still unclear whether aging exerts its effects via stimulation of excessive or dysregulated inflammatory responses. This hypothesis is supported by previous studies showing that aged animals have altered immune responses resulting from ischemic insult (Kharlamov et al, 2000;PopaWagner et al, 2007;Dinapoli et al, 2010;Sieber et al, 2011), intracerebral hemorrhage (Lee et al, 2009) or mechanical injury (Kyrkanides et al, 2001). However, mechanisms through which aging interacts with systemic inflammation to influence cerebrovascular pathologies remain unclear.…”
Section: Introductionsupporting
confidence: 62%
“…Although Nissl staining suggested that the hippocampus was spared direct injury by cortical photothrombosis and FJB-positive somata were not detected in the hippocampus at any time following photothrombosis, reduced NeuN IR in the hippocampus suggested some degree of neuronal dysfunction and/or a changed phosphorylation state of the NeuN protein (Lind et al, 2005). The distribution of increased GFAP IR was similar to that previously reported for the photothrombosis model (Bidmon et al, 2001b;Kharlamov et al, 2000;Oermann et al, 2004;Schroeter et al, 1995).…”
Section: Discussionsupporting
confidence: 85%
“…Studies using aged rodents demonstrated increased brain injury size and behavioral deficits, which were associated with modulation of the number or function of mononuclear phagocytes at the injury site [168,194,195]. Increased CD8 + T cells in the aged CNS were associated with compromised proinflammatory functions in microglia.…”
Section: Agingmentioning
confidence: 98%